DDIT3 Expression in Liposarcoma Development. (25th March 2014) - Kåbjörn Gustafsson, Christina; Engström, Katarina; Åman, Pierre
Abstract : Liposarcomas are mesenchymal tumors containing variable numbers of lipoblasts or adipocytes. The most common entities, well differentiated/dedifferentiated liposarcoma (WDLS/DDLS) and myxoid/round cell liposarcoma (MLS/RCLS), are both characterized by genetic rearrangements that affect the expression of the transcription factor DDIT3. DDIT3 induces liposarcoma morphology when ectopically expressed in a human fibrosarcoma. The role of DDIT3 in lipomatous tumors is, however, unclear. We have analyzed the expression of DDIT3 in 37 cases of liposarcoma (WDLS/DDLS n = 10, MLS/RCLS n = 16, and pleomorphic liposarcomas (PLS) n = 11) and 11 cases of common benign lipomas. Major cell subpopulations of WDLS/DDLS and MLS/RCLS tumors were found to express DDIT3 or the derived fusion protein, whereas PLS cases showed only a few positive cells. The lipomas contained large subpopulations expressing DDIT3. No correlation between numbers of DDIT3 expressing cells and numbers of lipoblasts/adipocytes was found. In vitro adipogenic treatment of two DDIT3 expressing cell lines induced lipid accumulation in small subpopulations only. Our results suggest a dual, promoting and limiting, role for DDIT3 in the formation of lipoblasts and liposarcoma morphology.